Body Training: Theatrical Creation Factors which Develop Motor Creativity for the Staging - Muñoz Salazar, Luz Elena (2021)
This article reports on the own research process that seeks to identify the factors of body training associated with theatrical creation that influenced the development of motor creativity for the staging dramaturgy of the monologue Marranadas (2007) by the playwright from Cali, Víctor Hugo Enríquez. The research was developed using the qualitative approach with the CCM design (Constant Comparative Method); for the documentary review of the blogs and the written works of the student, reading cards, audiovisual and correlative cards were used as instruments; which allowed us to identify that, the factors of body training associated with theatrical creation influencing the development of motor creativity are: the body as a blog and the shared corpo-dramaturgy. The research was carried out at the Bellas Artes Departmental Institute, Cali during 2006 and 2012.